Case Report: Vitamin C combined with multiple micronutrient deficiencies is associated with pulmonary arterial hypertension in children with autistic spectrum disorder - Sakamornchai, Wirada; Dumrongwongsiri, Oraporn; Siwarom, Sirinapa (Frontiers in Nutrition, 2022)
Children with developmental and behavioral problem including autistic spectrum disorders (ASD) may have inappropriate feeding behaviors, which leads to increase risk of multiple nutrient deficiencies. Vitamin C deficiency is one of the common nutrient deficiency reported in children with inappropriate feeding. This case report illustrates 2 cases of ASD children with a clinical presentation of pulmonary arterial hypertension, a rare presentation of vitamin C deficiency. Vitamin C supplementation, pulmonary vasodilator and supportive treatment were provided. Patients could recover from the illness and could be discharged from the hospital in a short time. In addition to vitamin C, the patients also had multiple micronutrient deficiencies. Nutrition counseling was given and micronutrient supplement was continued until follow up. Regular nutrition assessment and counseling among children with ASD are needed to prevent nutrient deficiencies which may lead to life-threatening complications.